A low‐cost digital calibration scheme for high‐resolution SAR ADC using Adaptive‐LMS. Issue 25 (3rd November 2022) - Yang, Yongkui; Yin, Tingting; Liu, Jiping; Yao, Enyi
Abstract: This paper presents a novel low‐cost digital calibration scheme using Adaptive‐LMS for high‐resolution SAR ADCs. This proposed Adaptive‐LMS is realized by perturbing adaptive analog offset and skipping several LSBs' calibration. Compared with a digital calibration scheme based on conventional LMS, the design saves not only die cost but also testing cost (less testing time). During the testing process, the proposed method requires only 16, 000 samples to calibrate the capacitor mismatch and the SNDR is improved from 54.1 dB to 68.1 dB for a 12‐bit SAR ADC.